Villages et quartiers à risque d'abandon Stratégies pour la connaissance, la valorisation et la restauration - Hadda, Lamia; Mecca, Saverio; PANCANI, GIOVANNI; Carta, Massimo; Fratini, Fabio; Galassi, Stefano; Pittaluga, Daniela (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
The issue of villages and neighborhoods at risk of abandonment is a common topic in many Mediterranean regions and is considered as a strategic point of the new European policies. The progressive abandonment of inland areas, with phenomena of emigration and fragmentation of cultural heritage, is a common trend in countries characterized by economic underdevelopment. This leads to the decay of architectural artifacts and buildings and problems with land management. Some aspects of this issue are also found in several urban areas. The goal of this research work is collecting international debates, discussions, opinions and comparisons concerning the analysis, study, surveys, diagnoses and graphical rendering of architectural heritage and landscape as well as demo-ethno-anthropological witnesses, typological-constructive stratifications, materials and technologies of traditional and vernacular constructions of historic buildings.